The Effect of Perceived Usefulness and Perceived Ease of Use on Behavioral Intention Mediated by User Satisfaction in E-Commerce Users - Elfrits Oematan, Mariano; Rahayu , Siti; Dyah , Juliani (Jurnal Ekonomi, 2024)
The purpose of the study is to determine perceived usefulness and perceived ease of use on behavioral intention mediated by user satisfaction in e-commerce users. The research method used is a quantitative method with a survey approach. Data collection technique by distributing questionnaires to respondents. The population in the study was 2568 students of the Faculty of Business and Economics with a sample of 97 respondents. The results of the study were (1) Perceived Usefulness has a significant effect on Behavioral Intention to Use, (2) Perceived Ease of Use has a significant effect on Behavioral Intention to Use, (3) Perceived Usefulness has a significant effect on Satisfaction, (4) Perceived Ease of Use has a significant effect on Satisfaction, (5) Satisfaction has a significant effect on Behavioral Intention to Use, (6) Perceived Usefulness has a significant effect on Behavioral Intention to Use mediated by satisfaction, (7) Perceived Ease of Use has a significant effect on Behavioral Intention to Use mediated by satisfaction,